Multiple Myeloma Case Developed During the Use of the Teriparatide - Zehra Erdemir; Ayşe İyiyapıcı Ünübol; Mustafa Ünübol; Esra Ercan Aktekin; İrfan Yavaşoğlu; Engin Güney (Türk Osteoporoz Dergisi)

(untitled)
Recombinant human parathyroid hormone (1-34) (rhPTH 1-34), teriparatide, is a class of anabolic therapy for treating severe osteoporosis. Although plasma cell dyscrasias are excluded among the known side effects of teriparatide treatment, their association in the form of case reports has been reported. PTH 1-34 stimulates osteoblasts and indirectly stimulates receptor activator of nuclear factor kappa-B ligand (RANKL), RANK and IL-6 with osteoclast stimulation. There are relationships between RANKL/OPG system and osteoclast and osteoblast activity in multiple myeloma. We report a case with multiple myeloma who developed malignant myeloma after teriparatide treatment.